Proceedings of the 2014 Workshop on Design, Quality and Deployment of Adaptive Video Streaming 2014
DOI: 10.1145/2676652.2676658
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adaptation Strategies on Perceived Quality of HTTP Adaptive Streaming

Abstract: Changing network conditions like bandwidth fluctuations and resulting bad user experience issues (e.g. video freezes) pose severe challenges to Internet video streaming. To address this problem, an increasing number of video services utilizes HTTP adaptive streaming (HAS). HAS enables service providers to improve Quality of Experience (QoE) and resource utilization by incorporating information from different layers. However, these adaptation possibilities of HAS also introduce new perceivable impairments such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…[11] found that neither smooth nor abrupt had a significantly better performance, although results in [12] indicate that slow gradual down switching was preferred. Also [13] did not find a significant difference for quality increases. Only for down switching smooth switching performed slightly better in terms of QoE than abrupt switching.…”
Section: Related Workmentioning
confidence: 75%
“…[11] found that neither smooth nor abrupt had a significantly better performance, although results in [12] indicate that slow gradual down switching was preferred. Also [13] did not find a significant difference for quality increases. Only for down switching smooth switching performed slightly better in terms of QoE than abrupt switching.…”
Section: Related Workmentioning
confidence: 75%
“…2) LabII and CSIII: The comprehensive technical report of these studies has been provided in [29]. Besides using different evaluation methodology, different adaptation sets were also used in two studies: In LabII, the video quality was varied along the compression dimension , whereas in CSIII the spatial resolution of the videos was varied.…”
Section: A Test Materials and Conditionsmentioning
confidence: 99%
“…Reference [2] investigates the impact of quality switches on the QoE in comparison to stalling events. Their results show that smooth switching only performs slightly better than abrupt switching.…”
Section: Background and Related Workmentioning
confidence: 99%
“…This may lead to a high number of quality switches, depending on the adaptation strategy. Even though stalling can be avoided in most cases, a high number of quality switches may also have a negative impact on the Quality of Experience (QoE) [1], [2]. A very passive adaptation strategy plays the video on a lower quality in order to keep the number of switches at a minimum.…”
Section: Introductionmentioning
confidence: 99%